188k views
18 votes
F(x) = 3x + 13; g(x) = 3x - 1
Find f(g(x)).
- help :(

User Syclonefx
by
4.7k points

1 Answer

12 votes

Answer:

f[g(x)] = 9x + 10

Explanation:

f[g(x)] means to replace the x of function f(x) with function g(x)

Given:

  • f(x) = 3x + 13
  • g(x) = 3x - 1

Therefore:

f[g(x)] = 3[g(x)] + 13

= 3(3x - 1) + 13

= 9x - 3 + 13

= 9x + 10

User Baptiste Costa
by
5.2k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.